(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article presents a comprehensive study on the cognitive processes of students in the field of general psychology. The research focuses on four key areas: memory, Dicka (a term used to describe a cognitive mechanism involving the integration of perception and imagination), thinking, and perceptual fantasy. Through a systematic analysis of these cognitive processes, this study aims to gain insights into how students perceive, remember, think, and generate mental imagery. The findings from this research provide valuable implications for educators and psychologists seeking to enhance learning and cognitive development in students.